Comparative Study of Building Envelope Cooling Loads in Al-Amarah City, Iraq - Qudama Al-Yasiri; Mushtaq A. Al-Furaiji; Ahmed K. Alshara (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
In recent years, the summer season in Iraq has become longer and hotter than before, leading to high cooling loads inside buildings and increased demand for electrical energy. The use of sustainable energy and insulation techniques for building envelopes are reasonable solutions for overcoming harsh weather conditions and reaching acceptable thermal comfort levels. In this study, a survey on more than 60 residential buildings in Al-Amarah City, Iraq, was conducted on 21 July 2018 to examine the nature of the most common construction materials used in the building envelopes. Furthermore, the cooling loads of building envelope elements, e.g. roof, external walls and windows, was calculated using the cooling load temperature difference/solar cooling load/cooling load factor method of ASHRAE. The results were tabulated and compared for each combination of elements. The results showed that reflective glass is the optimal choice for exterior windows. The 'clay